The parliamentary election in Ireland, February 2011 - GALLAGHER, MICHAEL; COURTNEY, MICHAEL (Elsevier, 2012)
The three-party coalition government formed in 2007 between Fianna Fail, the Green Party and the Progressive Democrats appeared to have a bulletproof majority, and there was every reason to expect that, like its two immediate predecessors, it would last the full five-year term. However, the global recession that began later that year and hit Ireland with full force in mid-2008 quickly reduced the likelihood that the government would survive until 2012. In September 2008 the crisis in the Irish banking system, which had over-stretched its loan books far beyond the realms of prudence in the previous decade, was finally exposed following the collapse of Lehman Brothers. After the event there were many questions as to why neither political actors, nor Ireland?s or the EU?s regulatory system, had noticed the many warning signs. On 29 September 2008 the Irish government guaranteed the deposits and loan books of the six Irish banks, and over the next two years it nationalised or effectively nationalised all but one of these. Consequently, the debts and losses of the banks were taken on by the taxpayer and a huge debt crisis emerged. Trust in and support for the government dropped sharply and never recovered, though the government remained in office for over two more years.
PUBLISHED
Keywords: Political science; Ireland; Elections